Problem of determining the order of execution of n jobs on m machines where each job has a different sequence of process - Eyzaguirre Tejada, Roberto (1999)
In this article is on H. Greenberg algorithm that is used to facilitate b'squeda a graphical solution for determining the order of execution of n jobs